Effects of synbiotics supplementation on anthropometric and lipid profile parameters: Finding from an umbrella meta-analysis - Musazadeh, Vali; Mohammadi Anilou, Maryam; Vajdi, Mahdi; Karimi, Arash; Sedgh Ahrabi, Sana; Dehghan, Parvin (Frontiers in Nutrition, 2023)
Several systematic reviews and meta-analyses have been carried out to assess the impact of synbiotics on lipid profiles and anthropometric parameters. In this regard, an umbrella meta-analysis was performed to provide a more accurate view of the overall impacts of synbiotic supplementation on lipid profile and anthropometric parameters. Databases such as PubMed, Scopus, Embase, Web of Science, and Google Scholar were searched for this study from inception to January 2022. A random-effects model was applied to evaluate the effects of synbiotic supplementation on lipid profile and anthropometric parameters. The methodological quality of eligible articles was evaluated using the AMSTAR2 questionnaire. The GRADE approach was used to evaluate the overall certainty of the evidence in the meta-analyses. Meta-analyses of 17 studies revealed significant decreases in body mass index (BMI) (ES: -0.13 kg/m2; 95% CI: -0.19, -0.06, p<0.001, I2 = 0.0 %, p = 0.870), BW (ES: -1.30 kg; 95% CI: -2.19, -0.41, p=0.004, I2=88.9 %, p<0.001), waist circumference (WC) (ES: -1.80 cm; 95% CI: -3.26, -0.34, p=0.016, I2=94.1 %, p<0.001), low-density lipoprotein cholesterol (LDL-C) (ES: -2.81 mg/dl; 95% CI: -3.90, -1.72, p<0.001, I2=95.1 %, p<0.001), total cholesterol (TC) (ES= -2.24 mg/dl; 95% CI: -3.18, -1.30, p<0.001, I2=94.5 %, p<0.001), and triglyceride (TG) (ES: -0.43 mg/dl; 95% CI: -0.79, -0.07, p= 0.019, I2=78.0 %, p˂ 0.001) but not high-density lipoprotein cholesterol (HDL-C) (ES: 0.23 mg/dl; 95% CI: -0.11, 0.56, p=0.193,I2=45.2 %, p=0.051) following synbiotic supplementation. The present umbrella meta-analysis suggests synbiotic supplementation can slightly improve lipid profile and anthropometric indices and might be a therapeutic option for obesity and its related disorders.